Facilitation of breathing by leptin effects in the central nervous system. (22nd June 2015) - Bassi, M.; Furuya, W. I.; Zoccal, D. B.; Menani, J. V.; Colombari, D. S. A.; Mulkey, D. K.; Colombari, E.
Abstract : A. Normal blood levels of leptin in a lean mice: Leptin action on Ob‐Rb receptors in the central nervous system (SNC) actives different intracelular pathways like ERK/STAT3/5 and IRS/PI3K that modulate energy balance and sympathetic nerve activity (SNA), respectively. The same pathways may also modulate breathing. B. Excess of leptin in obese mice: hyperleptinemia causes selective resistance to leptin in the CNS affecting energy balance (which intensify obesity) and breathing (causing breathing disorders). The activation of SNA is preserved and intensified causing hypertension. Abstract: With the global epidemic of obesity, breathing disorders associated with excess body weight have markedly increased. Respiratory dysfunctions caused by obesity were originally attributed to mechanical factors; however, recent studies have suggested a pathophysiological component that involves the central nervous system (CNS) and hormones such as leptin produced by adipocytes as well as other cells. Leptin is suggested to stimulate breathing and leptin deficiency causes an impairment of the chemoreflex, which can be reverted by leptin therapy. This facilitation of the chemoreflex may depend on the action of leptin in the hindbrain areas involved in the respiratory control such as the nucleus of the solitary tract (NTS), a site that receives chemosensory afferents, and the ventral surface of the medulla that includes the retrotrapezoid nucleus (RTN), a central chemosensitive area, and the rostral ventrolateral medulla (RVLM). Although the mechanisms and pathways activated by leptin to facilitate breathing are still not completely clear, evidence suggests that the facilitatory effects of leptin on breathing require the brain melanocortin system, including the POMC–MC4R pathway, a mechanism also activated by leptin to modulate blood pressure. The results of all the studies that have investigated the effect of leptin on breathing suggest that disruption of leptin signalling as caused by obesity‐induced reduction of central leptin function (leptin resistance) is a relevant mechanism that may contribute to respiratory dysfunctions associated with obesity.